Técnicas para superar la disgrafía en niños de primer año de educación general básica en laUunidad Educativa “Miguel Ángel León Pontón - Cano Miranda, Priscila Salomé (2024)
This research explores and determinte techniques for overcoming dysgraphia through grapho-motor and automation exercises in improving handwriting skills in first grade students at the Miguel Ángel León Pónton school. The methodological process involved a mixed approach, a non-experimental design, and was characterized as a proposal-oriented investigation. An observational technique was applied, using a data collection sheet focused on specific categories, with the participation of twenty-eight first-grade students. The results obtained showed that motor and graphic distortions, alterations, strokes, and handwriting that modified the meaning were more prevalent. Good posture and pencil grip allowed students to respond according to classroom instructions and the ability to perform strokes. Fine and gross motor skills were also observed in some students, as well as imitation and automation of the given information. Optimal biological maturation was confirmed in the group, which did not show any anatomical problems that hindered the understanding of the activities